Annotation and Comparative Genomics of Prokaryotic Transposable Elements - Ross, Karen; Zerillo, Marcelo Marques; Chandler, Mick; Varani, Alessandro M. [UNESP] (Springer Nature, 2024)
The data generated in nearly 30 years of bacterial genome sequencing has revealed the abundance of transposable elements (TE) and their importance in genome and transcript remodeling through the mediation of DNA insertions and deletions, structural rearrangements, and regulation of gene expression. Furthermore, what we have learned from studying transposition mechanisms and their regulation in bacterial TE is fundamental to our current understanding of TE in other organisms because much of what has been observed in bacteria is conserved in all domains of life. However, unlike eukaryotic TE, prokaryotic TE sequester and transmit important classes of genes that impact host fitness, such as resistance to antibiotics and heavy metals and virulence factors affecting animals and plants, among other acquired traits. This provides dynamism and plasticity to bacteria, which would otherwise be propagated clonally. The insertion sequences (IS), the simplest form of prokaryotic TE, are autonomous and compact mobile genetic elements. These can be organized into compound transposons, in which two similar IS can flank any DNA segment and render it transposable. Other more complex structures, called unit transposons, can be grouped into four major families (Tn3, Tn7, Tn402, Tn554) with specific genetic characteristics. This chapter will revisit the prominent structural features of these elements, focusing on a genomic annotation framework and comparative analysis. Relevant aspects of TE will also be presented, stressing their key position in genome impact and evolution, especially in the emergence of antimicrobial resistance and other adaptive traits.
Keywords: Adaptation; Bacterial fitness; Genome evolution; Genome plasticity; Recombination; Antibiotic resistance